Monitoring dan Evaluasi Pelatihan Pembinaan Kesadaran Bela Negara Lingkup Pekerjaan bagi Aparatur Sipil Negara Kementerian Lingkungan Hidup - Inge Salsabila Suryaman; Fitri Rosvianti; Sagita Ludyna Sanosie (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
The National State Defence Development Training (PKBN) plays a strategic role in shaping the National Defence character of employees in the workplace. Monitoring and evaluation is a systematic process that identifies the effectiveness and strengths of the PKBN program that has been implemented. The government, in its efforts to realize an advanced, prosperous, sovereign, and globally competitive Unitary State of the Republic of Indonesia, is committed to the vision of